The socio-economic module of the Berlin Aging Study II (SOEP-BASE): Description, structure, and questionnaire - Anke Boeckenhoff; Denise Saßenroth; Martin Kroh; Thomas Siedler; Peter Eibich; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
The Berlin Aging Study II (BASE-II) is a multidisciplinary study that allows for the investigation of how a multitude of health status factors as well as many other social and economic outcomes interplay. The sample consists of 1,600 participants aged 60 to 80, and 600 participants aged 20 to 35. The socio-economic part of BASE-II, the so called SOEPBASE, is conducted by the SOEP Group at the DIW Berlin. The surveyed socio-economic variables are fully comparable with the variables of the long running German SocioEconomic Panel Study (SOEP), which increases the analytical power of BASE-II. The socioeconomic data collected on the individual and on the household level are enriched with georeferenced context data ("neighbourhood data") in order to disentangle the interplay between individual, societal and regional determinants on individuals' health status and other outcome variables. Furthermore, as the BASE-II study is based on a convenience sample, the SOEP Group at the DIW provides weights for the BASE-II dataset that correct for selectivity bias. – – Die Berliner Altersstudie II (BASE-II) ist eine multidisziplinäre Studie, die es erlaubt, das Zusammenspiel verschiedenster Faktoren auf den Gesundheitsstatus und viele andere soziale und ökonomische Outcomes zu untersuchen. Die Stichprobe besteht aus 1.600 Teilnehmern zwischen 60 und 80 Jahren und 600 Teilnehmern im Alter von 20 bis 35 Jahren. Der sozioökonomische Teil von BASE-II wird von der SOEP-Gruppe am DIW Berlin durchgeführt und die entsprechenden SOEP-BASE-Daten mit den SOEP-Daten voll vergleichbar gemacht. Daten liegen sowohl auf der Individualebene als auch auf Haushaltsebene vor und werden mit geo-referenzierten Kontext-Daten (auf der Ebene von "Nachbarschaften") angereichert, sodass das Zusammenspiel von individuellen, gesellschaftlichen und regionalen Determinanten auf den individuellen Gesundheitszustand und andere Outcome-Variablen herausgearbeitet werden kann. Da die BASE-II Studie auf einem Convenience-Sample beruht, werden extensive Selektions-Analysen durchgeführt und darauf aufbauend wird der BASE-II Datensatz mit Gewichten versehen, die für Selektionsverzerrungen korrigieren.
Keywords: C81; C83; I12; I14; I24; I31; I32; J14; Y80; Z13; 330; Cohort Study; Berlin Aging Study; BASE-II; SOEP